ENTREPRENEURIAL SPIRIT ENHANCEMENT STUDENT AL-UMM ASWAJA ISLAMIC BOARDING SCHOOL THROUGH SKILLS ECOPRINT - Indupurnahayu, Indupurnahayu; Pasaribu, Popy Novita; Susetyo, Budi; Maulina, Dwi; Hamasah, Abdullah Azzam (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Entrepreneurship has an important role in economic and social development and is a strategic tool for countries that want to achieve economic independence. In Indonesia, one of the efforts to increase entrepreneurship is carried out through entrepreneurship development programs in Islamic boarding schools, such as those implemented at the Al-Umm Aswaja Islamic Boarding School. However, lack of motivation and limited entrepreneurial practices are obstacles. To overcome this, Creative Thinking and Ecoprint training was implemented as a solution to generate interest in entrepreneurship among students. The results of the analysis show that these two trainings succeeded in increasing students' understanding and interest in entrepreneurship, with the Ecoprint training providing a more significant impact. In conclusion, this training program is effective in encouraging students to plan and start businesses, thereby contributing to the development of entrepreneurship and creating economic opportunities in the Islamic boarding school community.